2013
DOI: 10.1007/s00520-013-1863-y
|View full text |Cite
|
Sign up to set email alerts
|

Surprising results regarding MASCC members' beliefs about spiritual care

Abstract: Background The purpose of the study was to better understand the practice and meaning of spiritual care among cancer care professionals and ultimately provide a rationale for developing internationally focused spiritual care guidelines. Methods We developed a 16-question survey to assess the spiritual care practices. We sent 635 MASCC members 4 e-mails each inviting them to complete the survey via an online survey service. Demographic information was collected. The results were tabulated, and summary statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 30 publications
0
28
0
Order By: Relevance
“…Traditionally the chaplain is the designated spiritual carer, M a n u s c r i p t 4 but the role of the medical team in spiritual care has been increasingly promoted. (5,6) This is a result of moves to reintroduce a biopsychosocialspiritual model of care into medicine (7) and research suggesting that a significant proportion of patients would like their physician to enquire about their spiritual needs (8,9). Furthermore, evidence suggests that healthcare is enhanced when the doctor is aware of strongly held religious and spiritual (R/S) beliefs.…”
Section: Introductionmentioning
confidence: 94%
“…Traditionally the chaplain is the designated spiritual carer, M a n u s c r i p t 4 but the role of the medical team in spiritual care has been increasingly promoted. (5,6) This is a result of moves to reintroduce a biopsychosocialspiritual model of care into medicine (7) and research suggesting that a significant proportion of patients would like their physician to enquire about their spiritual needs (8,9). Furthermore, evidence suggests that healthcare is enhanced when the doctor is aware of strongly held religious and spiritual (R/S) beliefs.…”
Section: Introductionmentioning
confidence: 94%
“…In studies of self-reported barriers to SC provision, reasons cited by nurses and physicians for infrequent SC provision include insufficient time to discuss R/S and personal discomfort with R/S. 1417 Although illuminating as to potential barriers at play, these studies do not examine the relationship of these barriers to actual SC provision to patients. Furthermore, there are other putative barriers that require investigation, such as the asymmetry between the U.S. population and medical professionals in religious characteristics, including religious affiliation and self-reported religiosity and spirituality; 13,18 these factors may prompt medical professionals to avoid R/S issues, rather than risk creating discomfort or offense.…”
Section: Introductionmentioning
confidence: 99%
“…A person might be described as more or less religious based upon how many times he or she attended religious services or participated in religious activities such as worship, prayer, or other religious actions (Koenig, King, & Benner Carson 2012). In contrast, spirituality is widely-acknowledged to have a broader definition than religiosity in which both religious and nonreligious perspectives are encompassed, as spirituality is not restricted by the boundaries of any one religious tradition and is frequently a self-defined concept (Breen et al 2006;McCarthy Veach et al 2003;Price et al 2007;Ramondetta et al 2013). Spirituality often centers on the search for meaning or purpose in life, and spiritual beliefs and practices aid a person in looking outside of the self for support and/or guidance in crisis situations (Breen et al 2006;D'Souza 2007;Seth et al 2011;Weil 2000).…”
Section: Introductionmentioning
confidence: 99%
“…A qualitative study of 130 pregnant women that asked how faith or spirituality impacted their pregnancy revealed that these women commonly found faith to provide guidance and support, protection, communication with God, strength, and help in making difficult choices (Jesse, Schoneboom, & Blanchard 2007). A patient's spiritual beliefs may provide comfort and reconciliation that could help ease difficult decisions (Anderson 2009;Ramondetta et al 2013;Seth et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation